The Role of Religious Education in Maintaining Students' Mental Health in the Digital Age - Aliffia, Kurnia Nur; Candrika, Ariibah Radita Ayu; Savana, Oseolla; Hidayati, Fippy; Ikhrom, Ikhrom; Junaedi, Mahfud (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
This study explores the role of Islamic Religious Education in maintaining students’ mental health amidst the challenges of the digital era. As technology rapidly transforms students' lifestyles, issues such as gadget addiction, cyberbullying, and social pressure increasingly affect their psychological well-being. This qualitative research adopts a descriptive approach to examine how Islamic Religious Education contributes to students' emotional resilience and moral stability. Data were collected through interviews, observations, and document analysis involving students, Islamic Religious Education teachers, parents, and school counselors. The findings reveal that the integration of Islamic values such as patience, gratitude, and self-reflection through Islamic Religious Education plays a significant role in fostering students' mental strength, especially in facing digital distractions and emotional distress. The study concludes that Islamic Religious Education not only functions as a cognitive learning process but also serves as a spiritual and psychological safeguard. Strengthening the contextual implementation of Islamic Religious Education and enhancing teacher competencies are recommended to support students’ mental well-being in a digital-driven environment.